Analyzing The Post-Pandemic Resilience-Based Communication Policies in Great Bandung Area Suburban Communities - Rulandari, Novianita; Talib, Soleman; Muksin, Isra; Yusuf, Maryani; Muhidin, Bustamin (Yayasan Ilomata, 2024)
The COVID-19 pandemic has profoundly impacted communities globally, testing their resilience and adaptability. This study examines the resilience-based communication policies implemented in the Greater Bandung suburban area in West Java, Indonesia, post-pandemic. Employing a qualitative case study approach, the research investigates the specific communication strategies used by local authorities and community organizations, assesses their effectiveness in fostering community resilience, and identifies the challenges and opportunities encountered in policy implementation. The findings reveal a multi-channel communication approach, emphasizing the importance of tailored messaging, stakeholder collaboration, and early preparedness communication. However, challenges remain in reaching marginalized groups and ensuring timely information dissemination. The research underscores the need for inclusive communication strategies, trust-building with communities, and localized messaging to enhance community resilience in future crises.